The Implementation Of Strategic Management In The Management Of State Assets: An Empirical Study At The Office Of The Ministry Religious Affairs Of Wonogiri Regency - Nur Kholistiani; Lilis Sulistyani (STIE AUB Surakarta, 2018)
This research is a kuantitatif research, that purpose was to determine empirically the implementation of asset management at the office of The Ministry Religious Affairs of Wonogiri Regency using the influence of leadership, organizational commitment, and strategic management as intervening variables. This study is a survey method based research. The used primary data was done by taking as 50 (fivety) employees at The Ministry Religious Affairs of Wonogiri Regency. Data in this research wald be obtained directly from the results of questionnaires. The analitycal tool used instrument test, linearity test, path analysis and regression with t test, F test and R2 test. This study result point that leadership had positive and significant influence on strategic management, organizational commitment had positive and significant impact on strategic management, leadership had positive and significant impact on asset management, organizational commitment had a positive and significant impact on asset management, strategic management has a significant positive effect on asset management. The simultaneous result of the test (F test) can be concluded as leadership variables, organizational commitment, strategic management have a positive and significant impact on asset management. The result of determination test shows that R Square total is 0,92, which means asset management variable is explained by leadership, organizational commitment, and strategic management of 92% and the rest of 8% is explained as other variable outside the research model. The results of path analysis shows that the indirect effect of leadership on asset management through strategic management is greater than the direct influence of leadership on asset management, the direct impact of organizational commitment to asset management is greater than the indirect influence of organizational commitment through strategic management. The indirect path of leadership through strategic management is the most dominant variable of its influence on asset management is the path chosen as the most effective path in asset management.Keywords: leadership, organizational commitment, strategic management, asset management.